External ultrastructure of Progonoia diatreta sp. nov. (Bacillariophyta, Scoliotropidaceae) differs from P. musca and P. intercedens comb. nov. - Lobban, Christopher S. (Phytotaxa, 2015)
Navicula musca was described by Gregory in 1857 as having moniliform areolae in unbroken striae; a detailed ultrastructural study by Schrader, who transferred the species to Progonoia in 1971, was consistent with the original description. However, going back at least to Peragallo & Peragallo at the turn of the 20th century, the same species has been described as having alveoli with fine puncta around the edge and a longitudinal break in the striae. I found examples of both forms in a collection of calcareous sand from Guam, examined them with light and scanning electron microscopy, and also examined authentic material of N. musca in the light microscope. I conclude that one of these taxa is consistent with N. intercedens, which must be removed from synonymy with P. musca, and that the form with the fine puncta is an undescribed species not previously observed ultrastructurally. This species, P. diatreta sp. nov., has an internal valve structure that clearly places it in Progonoia, but an external structure quite different from that of its congeners.